2018
DOI: 10.1159/000486912
|View full text |Cite
|
Sign up to set email alerts
|

TRPC3 Overexpression Promotes the Progression of Inflammation-Induced Preterm Labor and Inhibits T Cell Activation

Abstract: Background/Aims: To detect the expression of the TRPC3 channel protein in the tissues of women experiencing preterm labor and investigate its interaction with T lymphocytes, providing a theoretical basis for the clinical prevention of threatened preterm labor and the development of drug-targeted therapy. Methods: Forty-seven women experiencing preterm labor and 47 women experiencing normal full-term labor were included in this study. All included women underwent delivery via cesarean section; uterine samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…18,20,21 Also described in derived cell lines of human myometrium, are TRPCs, Orai, and STIM. 19,20,22,23,[34][35][36] Our results in rat myometrium also indicated that Orai1 channels participate in the maintenance of muscarinic agonist-induced action. Molecular evidence of [Ca 2+ ]i elevation, promoted by the activation of muscarinic receptors and mediated by Orai1 channels, has been obtained for some cell types.…”
Section: Discussionsupporting
confidence: 59%
“…18,20,21 Also described in derived cell lines of human myometrium, are TRPCs, Orai, and STIM. 19,20,22,23,[34][35][36] Our results in rat myometrium also indicated that Orai1 channels participate in the maintenance of muscarinic agonist-induced action. Molecular evidence of [Ca 2+ ]i elevation, promoted by the activation of muscarinic receptors and mediated by Orai1 channels, has been obtained for some cell types.…”
Section: Discussionsupporting
confidence: 59%
“…Studies assessing the underlying molecular mechanisms behind the embryo-uterine interplay are very scarce and molecular candidates involved in the early communication still need to be fully elucidated and characterized. Ion channels are potential candidates to govern signals and are emerging more often as important players in the field of reproductive medicine 42,43 . However, the fingerprint of ion channels in endometrial epithelial cells is very incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…These findings reveal the role of phospholipase C-like proteins in suppressing uterine smooth muscle contraction with a human relevance. In summary, our data show the PGR-B-specific modulation on multiple regulators in a signaling cascade for muscle contraction that includes the oxytocin receptor, the phospholipase C signaling, and a calcium channel of known contribution on laboring (69,71,74).…”
Section: Physiologymentioning
confidence: 69%